Global geoparks: Opportunity for developing or “toy” for developed? - Dmitry A. Ruban; Anna V. Mikhailenko; Natalia N. Yashalova; Alexey V. Scherbina (International Journal of Geoheritage and Parks, 2023)
Geoparks can provide socio-economical benefits to local communities, but their relative importance to developed and developing countries is yet to be fully realized. The present study aims at analyzing the correspondence of the UNSECO Global Geopark network to countries with different level of human development. The information about the geographical extent of this network and the human developed index is taken into account. Its analysis implies that global geoparks have strong presence in the countries with very high and high human development, but they are relatively rare in the countries with moderate and low human development. Less than 10% of global geoparks exist in the countries with the human development index below its median value. Examination of how social issues are stated in the official descriptions of these geoparks and on their web-pages indicates on its insufficient explanation in some cases. It is proposed to facilitate international mechanisms supporting geopark creation in developing countries.